An exploration of right-wing extremist incidents in Atlantic Canada. Issue 3 (2nd September 2021) - Hofmann, David C.; Trofimuk, Brynn; Perry, Shayna; Hyslop-Margison, Caitlin
ABSTRACT: The study of Canadian right-wing extremism from a security context is in its infancy, with only a handful of empirical and theoretical studies emerging on the topic within the last decade. With the increase of right-wing extremism violence in Canada such as the 2014 Moncton shooting and the 2017 Quebec City mosque attack, there is a pressing need to better understand the breadth, depth, and extent of Canadian right-wing extremism. The current paper presents the preliminary findings from a larger cross-Canadian research project on right-wing extremism and focuses exclusively on Atlantic Canada (New Brunswick, Nova Scotia, Newfoundland & Labrador, and Prince Edward Island). A comprehensive scoping of open-source documents of right-wing extremist incidents in Atlantic Canada from January 2000 to December 2019 and their related attributes were compiled into a dataset, and then used to explore the distribution, breadth, type, and extent of right-wing extremist activity in the Maritime provinces. Given the focus of previous research upon urban aspects of Canadian right-wing extremism, and that Atlantic Canada is more rural in comparison to the rest of Canada, the breakdown of occurrences of different types of right-wing extremist activities based upon rurality are also examined.